THE MORAL VALUES IN GAMBIRANOM DANCE: (Study Morality of Immanuel Kant) - Lista Salsabila, Nadia; Nursilah; Mutiara Sari, Kartika (International Journal of Performing Arts (IJPA), 2023)
Based on Immanuel Kant’s perspective about morality, this study aims to identify the moral values in Gambiranom dance that are worthy of being used as a guideline in reviving the disappearing moral values. The researcher used a discourse analysis method and a qualitative approach to understand the symbolic meaning of discourse. The discourse in this study was the Gambiranom dance. In collecting the data, the researcher conducted interviews, observations, literary reviews, and documentation studies. The researcher also used the Miles and Huberman model of analysis technique to analyze the data. This study resulted in two primary data, the Gambiranom dance Hasta Sawanda and the form of presentation. The data resulted in an interpretation of Hasta Sawanda in Gambiranom dance as good will and the presentation form of Gambiranom dance as act rightly, both from the perspective of moral values by Immanuel Kant. The two data produced praiseworthy values, bringing forth the highest or ultimate good (Summum Bonum). A dancer can achieve the highest good if they implement act rightly and good will by the rules of Surakarta’s style of classical Javanese dance. It is a condition where the dancer succeeds in wholly merging themselves into the character of Irawan, where the spectators or audience no longer see the dancer as a dancer but as the character of Raden Irawan, the Prabu Gambiranom.